Global Profiling of N-Glycoproteins and N-Glycans in the Diatom Phaeodactylum tricornutum - Xie, Xihui; Du, Hong; Chen, Jichen; Aslam, Muhammad; Wang, Wanna; Chen, Weizhou; Li, Ping; Du, Hua; Liu, Xiaojuan (Frontiers in Plant Science, 2021)
N-glycosylation is an important posttranslational modification in all eukaryotes, but little is known about the N-glycoproteins and N-glycans in microalgae. Here, N-glycoproteomic and N-glycomic approaches were used to unveil the N-glycoproteins and N-glycans in the model diatom Phaeodactylum tricornutum. Totally, 863 different N-glycopeptides corresponding to 639 N-glycoproteins were identified from P. tricornutum. These N-glycoproteins participated in a variety of important metabolic pathways in P. tricornutum. 12 proteins participating in the N-glycosylation pathway were identified as N-glycoproteins, indicating that the N-glycosylation of these proteins might be important for the protein N-glycosylation pathway. Subsequently, 69 N-glycans corresponding to 59 N-glycoproteins were identified and classified into high mannose and hybrid type N-glycans. High mannose type N-glycans contained four different classes, including Man-5, Man-7, Man-9 and Man-10 with a terminal glucose residue. Hybrid type N-glycan harbored Man-4 with a terminal GlcNAc residue. The identification of N-glycosylation on nascent proteins expanded our understanding of this modification at a N-glycoproteomic scale, the analysis of N-glycan structures updated the N-glycan database in microalgae. The results obtained from this study facilitate the elucidation of the precise function of these N-glycoproteins and are beneficial for future designing the microalga to produce functional humanized biopharmaceutical N-glycoproteins for the clinical therapeutics.